1998
DOI: 10.1038/bjc.1998.418
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary case teams: an approach to the future management of advanced colorectal cancer

Abstract: Summary The effective management of advanced colorectal cancer has traditionally been viewed in terms of treatment outcome measures such as efficacy (survival, objective response and palliation) and safety. Although these outcomes are of paramount importance and are essential for the evaluation of the effectiveness and tolerability of treatment, they do not take account of the global effect of therapy on patients, society and healthcare systems. Furthermore, they may not reveal important differences between tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…There is an increasing appreciation of the importance of the palliative effects of treatment in patients with advanced cancer; Redmond (1998) and Minsky (1998) have shown how the overall effectiveness of treatment can be enhanced by using therapies that combine increased well-being for patients with clinical efficacy in terms of objective response and survival. In the present phase III clinical trials, clinically significant palliative benefits were obtained to a similar extent with raltitrexed and 5-FU + LV in terms of weight gain, improvements in performance status and reductions in disease symptoms (e.g.…”
Section: Objective Response Ratesmentioning
confidence: 99%
“…There is an increasing appreciation of the importance of the palliative effects of treatment in patients with advanced cancer; Redmond (1998) and Minsky (1998) have shown how the overall effectiveness of treatment can be enhanced by using therapies that combine increased well-being for patients with clinical efficacy in terms of objective response and survival. In the present phase III clinical trials, clinically significant palliative benefits were obtained to a similar extent with raltitrexed and 5-FU + LV in terms of weight gain, improvements in performance status and reductions in disease symptoms (e.g.…”
Section: Objective Response Ratesmentioning
confidence: 99%
“…Usually, the multidisciplinary team (MDT) of colorectal cancer consists of several departments; imaging and pathology make the diagnosis while colorectal surgery, oncology, radiotherapy and palliative care provide the therapy 9, 10. The MDT mode can improve the survival of rectal cancer, and is recommended by many guidelines 11-13. However, there is few researches report the importance of MDT in the assessment of MRI and the influence of MDT for accurate staging and therapy strategy selecting.…”
Section: Introductionmentioning
confidence: 99%
“…After examining the probability and frequency of emergency care utilization presented by other variables, we found that the deterioration of health conditions, such as advanced cancer staging and increase in outpatient visits and inpatient visits, increases the probability and frequency of emergency care utilization and there were significant differences among groups, which is consistent with the results of many studies on survival of patients with colorectal cancer. [ 11 , 32 , 33 ] Some studies suggested that patients with advanced colorectal cancer received the best quality of overall treatment with MDT, [ 34 , 35 ] which means that with the advance of colorectal cancer, the challenges to diagnosis, treatment and care would be greater. We hope to see more investigators dedicate their research in this area in the future.…”
Section: Discussionmentioning
confidence: 99%